The PESCO agreement and the future of the European common defence - Loi, S. (Europe as Global Actor, 2018)
2016 and 2017 have been fundamental years for the development of a European common defence framework. After years characterized by small or no improvements related to the creation of the foundations of a European military force structure, the PESCO agreement possibly set up the path for a stronger military cooperation in the EU. In this paper, the past, present, and future of this project will be analysed to try to assess, on the one hand, the reasons why in the last two years such an improvement culminating with PESCO has been possible, and, on the other hand, how this agreement will be put into practice both at a national and European level. At first, it will be considered the role that a triad of interconnected elements played to boost the process that eventually lead to the PESCO agreement. This triad is composed by the Brexit referendum, the presentation of the EU Global Strategy and its adoption, and the election of Donald Trump in the US. After the analysis of these elements, we will analyse the impact that the PESCO agreement had at a national, EU and international levels. Finally, this paper will try to foresee how this agreement will be implemented in the near future, and will try to assess if PESCO could be considered a starting point for a future integrated European defence, and at which level.